2020
DOI: 10.12659/msm.926780
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin Promotes the Apoptosis and Inhibits the Proliferation, Migration, and Invasion of Cervical Cancer Cells by Downregulating SULT2B1 Expression

Abstract: Background Cervical cancer threatens women’s health worldwide. Verteporfin (VP), a small-molecule YAP1 inhibitor, inhibits cancer cell growth. This study investigated whether VP could inhibit the proliferation and promote the apoptosis of cervical cancer cells by decreasing SULT2B1 expression. Material/Methods Normal and cancerous cervical cell proliferation after VP treatment was detected by CCK-8 assay. HeLa cell migration, invasion, and apoptosis after VP treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…In the present study, we revealed that the mRNA and protein levels of SULT2B1 were significantly downregulated in ESCC tissues compared to matched tumor-adjacent tissues. This finding was consistent with TCGA data, but there are also some reports to the contrary indicating that the expression of SULT2B1 is increased in some other tumors, such as cervical cancer, 24 hepatocellular carcinoma, 11 and colorectal carcinoma. 25 CpG islands are located in the promoter region and transcriptional start site of a gene, which represent a high enrichment of CpG sites and are prone to DNA methylation.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we revealed that the mRNA and protein levels of SULT2B1 were significantly downregulated in ESCC tissues compared to matched tumor-adjacent tissues. This finding was consistent with TCGA data, but there are also some reports to the contrary indicating that the expression of SULT2B1 is increased in some other tumors, such as cervical cancer, 24 hepatocellular carcinoma, 11 and colorectal carcinoma. 25 CpG islands are located in the promoter region and transcriptional start site of a gene, which represent a high enrichment of CpG sites and are prone to DNA methylation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we developed a 12-LMRG recurrence signature using 334 early-stage LUAD patients from the TCGA database. This signature includes LDHA, NSDHL, TP53INP2, FLT1, IRS1, ELOVL7, AGPS, FHL2, MED6, PLIN3, VDAC1, and SULT2B1, most of which were revealed to be correlated with tumor proliferation and progression (39)(40)(41)(42)(43)(44)(45)(46)(47). For instance, NSDHL, a crucial enzyme for cholesterol biosynthesis, has been reported to promote metastasis in triple-negative breast cancer (48).…”
Section: Discussionmentioning
confidence: 99%
“…YAP and TAZ play important roles in the Hippo (Hpo) and receptor tyrosine kinase (RTK) signaling pathways and are proven onco-proteins in several tumor types, including GBMs ( Figure 1 A) [ 92 , 93 , 94 , 95 ]. Previous studies have shown that VP has cytotoxic effects in GBM cells and cells of other cancer types including colon, endometrial, cervical, breast, pancreatic, and melanoma cancers [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. Porphyrins and their precursors have been the subject of intensive development for brain tumor therapy and intraoperative brain tumor imaging because GBM and glioma cells readily absorb these molecules in vitro and in vivo in animal models and patients [ 104 , 105 , 106 ].…”
Section: Repurposing a Drug For Macular Degenerationmentioning
confidence: 99%